Multilingual Practices in Indonesian Social Media Communication: Evidence from a Digital Sociolinguistic Survey - Mandra Saragih; M Afiv Toni Suhendra Saragih (English Teaching and Linguistics Journal (ETLiJ), 2026)
The rapid growth of social media has transformed multilingual communication practices and intensified the occurrence of code-mixing and code-switching in digital interactions. This study investigates multilingual practices among Indonesian social media users by examining the influence of social identity, digital community affiliation, and language prestige within the framework of digital sociolinguistics. A quantitative approach employing a correlational survey design was adopted involving 312 Indonesian social media users selected through proportional random sampling. Data were collected using a 35-item Likert-scale questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis with the assistance of IBM SPSS Statistics 27. The findings revealed that multilingual practices among Indonesian users were generally high, with language prestige emerging as the strongest predictor, followed by social identity and digital community affiliation. Collectively, these variables explained 62.4% of the variance in multilingual practices. The study confirms that multilingual communication in social media is a socially situated and technologically mediated phenomenon rather than merely a reflection of bilingual competence. The findings contribute to the development of digital sociolinguistics and provide implications for multilingual literacy and language education in contemporary digital environments.